Relation Of Inter Implants / Inter Dental Papillae After Scalloping Of Crest Bone Of The Jaws (New Technique) - Radhi, Munther M. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: The aims of this study is to determine the success of creating an inter implant / inter dental papillae after scalloping the crest of the jaw bones before placement of dental implant and compare this new technique with other techniques for creation of inter dental/inter implant papillae MATERIALS AND METHODS: A fifty five dental implantation were carried out for twenty one patients . Two stage dental implantation technique was done for all the patients .In this new technique scalloping of the bone was carried out before placement of the dental implant . RESULTS: The results of the present study indicates that the scalloping of the crest bone is consider as a best method for creation of inter implant / inter dental papillae and achieving an esthetically satisfying result before placement of the dental implants.. CONCLUSIONS: Scalloping of the crest bone make a good foundations that are essential for maintaining/creating papilla.